Embracing diversity through inclusive pedagogy: a comparative study of university faculty attitudes, competencies, and perceived challenges in Romania and Latvia - Marin, Elena; Briede, Liene; Kravale-Pauliņa, Mārīte; Presņakova, Irina (Frontiers in Education, 2025)
University faculty face multifaceted challenges when facilitating inclusive learning activities in courses attended by diverse student audiences. Their attitudes toward inclusive learning play a crucial role in shaping their approach; while some faculty members enthusiastically embrace inclusivity for its potential to enhance student engagement, others express uncertainty about managing diverse groups or harbor skepticism regarding its effectiveness. To successfully design and implement inclusive strategies, faculty need a comprehensive skill set and resources, including the ability to create inclusive learning activities, manage group dynamics within diverse classrooms, and effectively utilize technology. Challenges such as ensuring cultural sensitivity, accommodating different learning styles, overcoming language barriers, and handling complex group interactions significantly affect the efficacy of inclusive learning. Furthermore, limited resources, such as insufficient time and a lack of institutional support, often hinder these efforts. This study investigates the attitudes, capabilities, and concerns of university faculty from Romania (the University of Bucharest) and Latvia (Daugavpils University) regarding inclusive learning facilitation. Employing a mixed-methods design, the quantitative phase surveyed 33 faculty members (20 Romanian, 13 Latvian) using a structured survey focused on core inclusive pedagogy principles. The qualitative phase comprised semi-structured interviews with five faculty members from each country, providing in-depth insight via thematic content analysis. The findings indicate that faculty in both countries demonstrate a willingness to adapt teaching methodologies to meet varied learning needs, reflecting a proactive commitment to inclusive education. Additionally, positive responses highlight efforts to increase awareness about students’ learning requirements, adapt to diverse learning approaches, and foster perspective-taking in discussions related to cultural, social, and other differences without judgment.